Nutrients versus emerging contaminants–Or a dynamic match between subsidy and stress effects on stream biofilms. (May 2016) - Aristi, I.; Casellas, M.; Elosegi, A.; Insa, S.; Petrovic, M.; Sabater, S.; Acuña, V.
Abstract: Freshwater ecosystems are threatened by multiple anthropogenic stressors, which might be differentiated into two types: those that reduce biological activity at all concentrations (toxic contaminants), and those that subsidize biological activity at low concentrations and reduce it at high concentrations (assimilable contaminants). When occurring in mixtures, these contaminants can have either antagonistic, neutral or synergistic effects; but little is known on their joint effects. We assessed the interaction effects of a mixture of assimilable and toxic contaminants on stream biofilms in a manipulative experiment using artificial streams, and following a factorial design with three nutrient levels (low, medium or high) and either presence or absence of a mixture of emerging contaminants (ciprofloxacin, erythromycin, diclofenac, methylparaben, and sulfamethoxazole). We measured biofilm biomass, basal fluorescence, gross primary production and community respiration. Our initial hypotheses were that biofilm biomass and activity would: increase with medium nutrient concentrations (subsidy effect), but decrease with high nutrient concentrations (stress effect) (i); decrease with emerging contaminants, with the minimum decrease at medium nutrient concentrations (antagonistic interaction between nutrients subsidy and stress by emerging contaminants) and the maximum decrease at high nutrient concentrations (synergistic interaction between nutrients and emerging contaminants stress) (ii). All the measured variables responded linearly to the available nutrients, with no toxic effect at high nutrient concentrations. Emerging contaminants only caused weak toxic effects in some of the measured variables, and only after 3–4 weeks of exposure. Therefore, only antagonistic interactions were observed between nutrients and emerging contaminants, as medium and high nutrient concentrations partly compensated the harmful effects of emerging contaminants during the first weeks of the experiment. Our results show that contaminants with a subsidy effect can alleviate the effects of toxic contaminants, and that long-term experiments are required to detect stress effects of emerging contaminants at environmentally relevant concentrations. Graphical abstract: Highlights: Biofilms in artificial streams were subject to nutrients and emerging contaminants. Stress effects by emerging contaminants emerged only after 3 weeks of exposure. Nutrients can temporarily alleviate the harmful effects of emerging pollutants. Long-term experiments are needed to assess effects of emerging contaminants. Abstract : Moderate nutrient concentrations might temporarily alleviate the stress effects caused by emerging contaminants.